Analisis dan Perancangan (E-Raport) Berbasis Web dengan Metode Prototype (Studi Kasus SMAN 9 Tangerang Selatan) - Fauzan Azhima Fil Ramadhan; Muhammad Yunus Rangkuti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
SMA Negeri 9 Kota Tangerang Selatan is an ICT-based model school. In the academic process, especially the assessment still uses Microsoft Excel to store data, so that it can cause data redundancy and human errors, as well as provide delays in information to students / guardians of students. The purpose of this study is to design an academic system in processing the necessary assessment data according to the needs of students and schools, the author tries to make "Web-Based Analysis and Design (E-Report Card) with the Prototype Method" at SMA Negeri 9 Kota Tangerang Selatan, with the tools which is made according to the existing analysis problems in the school. In this study, the research methodology used was data collection methods, namely by interview and observation, while the development method used the Prototype method. The programming language used is Hypertext Preprocessor (PHP) and My Structure Query Language (MySQL) as its database. The results of this study are in the form of an academic information system that can help students / guardians in viewing reports on teaching and learning activities and minimizing errors in data entry.